United States : 2010 Article IV Consultation-Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2010)
The U.S. economy is recovering from a financial crisis, but remains vulnerable to shocks. Executive Directors welcomed health care reform, fiscal stabilization, and the Financial Sector Assessment Program (FSAP) assessment, which acknowledged that the financial system has strengthened. Directors underscored the risks in the over-the-counter (OTC) derivatives markets, revitalizing private securitization, and reforms to the housing finance system, including government-sponsored enterprises (GSEs). Directors appreciated the United States for promoting multilateral economic management. Directors assessed that U.S. economic policy could help secure global growth and stability through fiscal consolidation, which could reduce account deficit, and strengthen the financial sector.